1988
DOI: 10.1113/jphysiol.1988.sp017412
|View full text |Cite
|
Sign up to set email alerts
|

Time‐resolved X‐ray diffraction studies on the effect of slow length changes on tetanized frog skeletal muscle.

Abstract: SUMMARY1. The mechanism of the enhancement and the deficit of isometric force by slow length changes in frog skeletal muscle was studied with the time-resolved X-ray diffraction technique, using intense X-rays of synchrotron radiation.2. When a tetanized muscle was slowly stretched by 4 % from sarcomere lengths 2-3-2-4 ,um, the force rose to a peak during stretch and then decreased to a steady level 10-15 % higher than that immediately before stretch.3. The intensity of the 1,1 equatorial reflection decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
(30 reference statements)
2
20
0
Order By: Relevance
“…Mare´chal and Plaghki (1979) suggested that force depression might be caused by a stress-induced inhibition of cross-bridge attachments in the overlap zone that is formed between actin and myosin filaments as the muscle shortens. Herzog (1998) refined this idea by speculating that the compliant actin filaments (Amemiya et al, 1988;Goldman and Huxley, 1994;Kojima et al, 1994;Wakabayashi et al, 1994) might be stretched in the isometric contraction prior to shortening, and that this stretching would cause a reorientation of the actin attachment sites (Daniel et al, 1998) which in turn would decrease the probability of crossbridge attachments. This theory would require that force depression is dependent on the force and work performed in the shortening phase and is independent of the speed of shortening.…”
Section: Discussionmentioning
confidence: 94%
“…Mare´chal and Plaghki (1979) suggested that force depression might be caused by a stress-induced inhibition of cross-bridge attachments in the overlap zone that is formed between actin and myosin filaments as the muscle shortens. Herzog (1998) refined this idea by speculating that the compliant actin filaments (Amemiya et al, 1988;Goldman and Huxley, 1994;Kojima et al, 1994;Wakabayashi et al, 1994) might be stretched in the isometric contraction prior to shortening, and that this stretching would cause a reorientation of the actin attachment sites (Daniel et al, 1998) which in turn would decrease the probability of crossbridge attachments. This theory would require that force depression is dependent on the force and work performed in the shortening phase and is independent of the speed of shortening.…”
Section: Discussionmentioning
confidence: 94%
“…There are several possible mechanisms at work: a stretch-induced phosphorylation of myosin light chains (52), a disordering of the myofilament lattice (53), or an increase in the duration of attachment (dwell time) (3). …”
Section: Introductionmentioning
confidence: 99%
“…Stretch after activation may induce cross-bridge phosphorylation (57), myofilament-lattice disordering (53), and/or repartitioning of the cross-bridge population between the “force-bearing” and “non-force-bearing” molecular states (58-61). In the first case, the phosphorylated myosin light chains would bend myosin heads towards the actin filament (62,63).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanism of this phenomenon was pursued in a time-resolved X-ray diffraction study, in which equatorial reflection intensities were measured to monitor the number of myosin heads that attach to or stay in the vicinity of actin [5]. In twitch contractions, a shortening step induces the intensities to approach their resting values [5], while only a small, if any, effect was observed in tetanus [1,4]. These results suggest that at low [Ca 2+ ] i the detached myosin heads do not reattach to actin, but move away from it towards their resting positions on the myosin filament backbone.…”
Section: Introductionmentioning
confidence: 99%